Debt Dilution in 1920s America: Lighting the Fuse of a Mortgage Crisis - Natacha Postel-Vinay (European Historical Economics Society (EHES), 2014)
An explanation of the Great Depression based on mortgage debt via the banking channel has been downplayed due to the conservatism of mortgage contracts at the time. Indeed, maturities were particularly short compared to today's average terms (around three years), and loan-to-value ratios often did not exceed 50 per cent. Using newly-discovered archival documents and a newly-compiled dataset from 1934, this paper uncovers the darker side of 1920s U.S. mortgage lending: the so-called "second mortgage system." As borrowers often could not make a 50 per cent down payment, a majority of them took on second mortgages at usurious rates. As theory predicts, debt dilution, even in the presence of seniority rules, can be highly detrimental to both junior and senior lenders. The probability of default on first mortgages was likely to increase, and commercial banks were more likely to foreclose. Through foreclosure they would still be able to retrieve 50 per cent of the property value, but often after a protracted foreclosure process - a great impediment to bank survival in case of a liquidity crisis. This paper is thus a timely reminder that second mortgages, or "piggyback loans" as they are called today, can be hazardous to lenders and borrowers alike. It provides further empirical evidence that debt dilution can be detrimental to credit.
Keywords: G11; G21; N22; 330; Great Depression; Commercial Banks; Portfolio Choice; Mortgage